Analysis of the fiscal and health impact of increasing tobacco excise taxes in Ukraine - Biljana Jovanovikj; Nora Kungl; Kristijan Fidanovski; Hana Ross (The Vienna Institute for International Economic Studies (wiiw), 2024)
This policy note presents simulation estimates for the fiscal and health impact of raising tobacco taxes in Ukraine through the Tobacco Excise Tax Simulation Model (TETSiM). It outlines two scenarios for tax reform, which differ in terms of the scale and type of the tax increases, as well as of their application to different tobacco products. Both scenarios reveal clear fiscal and health benefits, thus providing compelling evidence for increasing tobacco taxes in Ukraine. We estimate that by 2028 the tax reform would bring in between EUR 3.69bn (UAH 157.8bn) and EUR 5.22bn (UAH 223.7bn) of additional tax revenue, boosting total tobacco tax revenue by between 39.3% and 68.9%, while preventing between 65,000 and 165,000 smoking-related deaths. The results also reveal considerable revenue gains if there were more rapid excise tax increases without any tax advantage being given to heated tobacco products.
Keywords: H24; I18; 330; Excise; Taxation; Tobacco; Smoking